Tariq Ramadan’s View on Western Muslims Identity: Between Nation and God’s Revelation - Fardana Khirzul Haq; Muhammad Shulthoni; Fahrudin Mukhlis (Universitas Muhammadiyah Malang, 2022)
The Western civilization is often considered to be more advanced than any other civilizations. Many people who think that western civilization is always in contradiction with Islamic values. Such this thing, it is written by Samuel P. Huntington that the West would have clash against Islam. The tragedy of 11 September 2001 was a historic event that made the world condemned this action. Some Muslim terrorists launched an attack on the West. Since then, the Western Countries are always alert to everything related to Islam. They think Islam is a threat to the survival of democracy and secularism. Tariq Ramadan Suggested that western Muslims must understand their identity as Western Muslims in order to be accepted in the West and tackle all negative views of Western people which are against them. They can have multiple identities depending on the situation they faced. There are four principles in their identity they are Faith, the understanding of the text and context, education (teaching) and participation. By participating without losing the first of those four principles, means Muslims able and should participate in realizing the integration of Western culture, with carrying on Islamic Values in order to be a significant contribution which equals Islamization.